Vitellogenin genes A1 and B1 are linked in the Xenopus laevis genome. - Wahli, W (1982)
Genomic clones containing the Xenopus laevis vitellogenin gene B1 have been isolated from DNA libraries and characterized by heteroduplex mapping in the electron microscope, restriction endonuclease analysis, and in vitro transcription in a HeLa whole-cell extract. Sequences from the 3'-flanking region of the previously isolated A1 vitellogenin gene were found in the 5'-flanking region of this B1 gene. Thus, the two genes are linked, with 15.5 kilobase pairs of DNA between them. Their length is about 22 kilobase pairs (A1 gene) and 16.5 kilobase pairs (B1 gene) and they have the following arrangement: 5'-A1 gene-spacer-B1 gene-3'. The analysis of heteroduplexes formed between the two genes revealed several regions of homology. Both genes are in the same orientation and, therefore, are transcribed from the same DNA strand. The possible events by which the vitellogenin gene family arose in Xenopus laevis are discussed.